If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3y = 2y + -5 Reorder the terms: 3y = -5 + 2y Solving 3y = -5 + 2y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-2y' to each side of the equation. 3y + -2y = -5 + 2y + -2y Combine like terms: 3y + -2y = 1y 1y = -5 + 2y + -2y Combine like terms: 2y + -2y = 0 1y = -5 + 0 1y = -5 Divide each side by '1'. y = -5 Simplifying y = -5
| f+f+f= | | 6v+18=35t | | d*d= | | (b+2)[(b+3)x-7]=b^2+4b+4-2b | | 4acosx=a+1 | | ln(2x^2+9x-5)=1+ln(x^2+2x-15) | | 15=-d+20 | | y(y+8)= | | 8n+1-6n+5=-4(-6-3n)-8(-1+n) | | -98k=7+4k | | 5n-25+4=8n+3 | | 5+3r=5r+12 | | -6y-3=3-3y | | 2=35x-13 | | 19x+26=121 | | 4t-6=5(t+5) | | 19x+26=21 | | 4n-12=13-4n | | 13x-2(3x+6)= | | -8n+12=-4n-4 | | 2n^2+11n+10=0 | | r^2-8r-20=0 | | 7-7=18x+8x | | 3(x+8)=3x+12 | | x/2=-30+35 | | 3x+4x^2=56 | | -4+10=12x-5-11x | | 3(v-2)-5v=-2(v+2) | | 3(2x-5)=7(x+2) | | v^2+6v-7= | | -6(u+1)+8u=2(u-3) | | 5x+9x+2+x= |